The Spanish Body Image State Scale: Factor Structure, Reliability and Validity in a Colombian Population - Mebarak Chams, Moisés; Tinoco, Laura; Mejia-Rodriguez, Dania; Martinez-Banfi, Martha L.; Preuss, Hanna; Hammerle, Florian; Vélez, Jorge I.; Kolar, David R. (Frontiers in Psychology, 2019)
Objective: Body image is a construct highly dependent to culture and ethnicity. Furthermore, recent studies revealed that body image is not only a trait, but also a momentary state subject to change in diverse situational contexts. However, cultural influences on momentary body image have not been sufficiently investigated. To assess the influence of Latin American culture on momentary body image and to enable its comparison to Western countries, the Spanish translation of an existing state body image scale such as the Body Image States Scale is needed. In addition, the factor structure, reliability and general validity of the Spanish BISS (S-BISS) should be evaluated prior to application in diverse situational contexts. Method: We conducted a cross-sectional study evaluating 1137 individuals between the ages of 18 to 28 years from Barranquilla, Colombia, South America. The original BISS, which assesses body satisfaction, was translated from English to Spanish. Factorial structure, internal consistency and convergent/divergent validity were assessed. Results: Exploratory and confirmatory factor analyses revealed that a one-factor model with correlated items best described the factorial structure present in the BISS questionnaire. The coefficient of internal consistency was α = 0.92 (MacDonalds ω = 0.93), with similar results for men and women. Significant differences between males and females were found with lesser body satisfaction in females (W = 163260, p =.016). Lower S-BISS scores indicating less body satisfaction were associated with higher BMI (r = -0.287, p < .001) and obtained in participants who were currently on a diet (t1135 = -3.98, p < .001). The S-BISS was negatively correlated with a trait body image measurement assessing body dissatisfaction (Body Shape Questionnaire, r = -.577, p < .001) and a psychopathology questionnaire (Brief Symptom Inventory 53,r = -.331, p<.001). Conclusion: The S-BISS is a valid and reliable instrument to assess body image in the Colombian population, and exhibits similar psychometric properties to those of the original version. Future studies should examine whether the S-BISS captures change in state body image when applied in diverse situational contexts.